Impact and Management Research: Exploring Relationships between Temporality, Dialogue, Reflexivity and Praxis. (January 2017) - MacIntosh, Robert; Beech, Nic; Bartunek, Jean; Mason, Katy; Cooke, Bill; Denyer, David
Abstract : This paper introduces the special issue focusing on impact. We present the four papers in the special issue and synthesize their key themes, including dialogue, reflexivity and praxis. In addition, we expand on understandings of impact by exploring how, when and for whom management research creates impact and we elaborate four ideal types of impact by articulating both the constituencies for whom impact occurs and the forms it might take. We identify temporality as critical to a more nuanced conceptualization of impact and suggest that some forms of impact are performative in nature. We conclude by suggesting that management as a discipline would benefit from widening the range of comparator disciplines to include disciplines such as art, education and nursing where practice, research and scholarship are more overtly interwoven.